The role of motivation factors in education for the development of student’s environmental leadership in HEIs - Rudyshyn, Serhii; Truskavetska, Iryna; Romanyuk, Svitlana; Vakal, Anatolii; Hnatyuk, Vitaliy (Intelektual Pustaka Media Utama, 2024)
This study aimed to explore the motivational factors influencing the development of environmental leadership qualities among students in higher educational institutions (HEIs). The study used surveys based on the methods of Zhang and Nunez Alonso, the Karpenko criteria, and the methods of Chen and Semedo. The study revealed that the proposed program, designed to enhance motivation and foster environmental leadership qualities, positively impacted students' motivation. Approximately one-third of students exhibited only an elementary level of environmental culture, indicating a lack of focus on environmental protection. However, applying the proposed approach increased motivation, environmental culture, and environmental leadership among students. Furthermore, a correlation was identified between motivation factors, environmental culture, and environmental leadership qualities. Future research should explore strategies for promoting ecological behavior among students, schoolchildren, and adults.